THE EFFECT OF STUDENTâS PERCEPTION ABOUT CLASSROOM MANAJEMENT AND STUDENTâS INTEREST TOWARD ECONOMIC SUBJECT RESULT AT TENTH GRADE STUDENTâS OF SMAN 16 PADANG - Putri, Lisa Wilanda (Pendidikan Ekonomi, 2014)
The research are concudated to analyze the effect of studentâs perception about classroom manajement and studentâs interest toward economic subject result at tenth grade studentâs of sman 16 padang. This was an descriptive and assosiatif research. The sampling was clone by simple random sampling. The sample in this research are about 153 students of tenth grade. Instrumen used is questionnaire . Based on the resultof item analysis, it was revealed that t value = 21,566. Hypothesis test used spss softfware 16.0 version. Based on the analysis abtained that f value = 389,712 while f tabel = 3 06, because F value > F table, the hipothesis was received it can be concluded that there is positive effect and significat result between studentâs interest and result of study in economic subject at tenth grade students.